2013
DOI: 10.1099/ijs.0.047613-0
|View full text |Cite
|
Sign up to set email alerts
|

Aureobasidium thailandense sp. nov. isolated from leaves and wooden surfaces

Abstract: Aureobasidium thailandense sp. nov. is described from cultures of material collected on leaves and wooden surfaces in Thailand and the type isolate is NRRL 58539T. Phylogenetically it is distinct from other species of the genus Aureobasidium. Phenotypically it is distinguished by its cardinal growth temperatures, salt tolerance and production of reddish brown hyphal pigmentation in PDA cultures, but micro-morphologically it is not clearly distinguishable from Aureobasidium pullulans. Unlike A. pullulans, A. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
(45 reference statements)
0
37
0
1
Order By: Relevance
“…The most recently described species of Aureobasidium are A. leucospermi Crous [47], A. proteae (Joanne E. Taylor & Crous) Joanne E. Taylor & Crous 2011 [47], and A. thailandense S.W. Peterson, Manitchotpisit & Leathers [48].
Figure 1 The Aureobasidium pullulans varieties.
…”
Section: Introductionmentioning
confidence: 99%
“…The most recently described species of Aureobasidium are A. leucospermi Crous [47], A. proteae (Joanne E. Taylor & Crous) Joanne E. Taylor & Crous 2011 [47], and A. thailandense S.W. Peterson, Manitchotpisit & Leathers [48].
Figure 1 The Aureobasidium pullulans varieties.
…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, phenotypic identification does not linier with genotype approach (Kurtzman & Suzuki, 2010). As well found in genera of Aureobasidium (Zalar et al, 2008;Peterson et al, 2013). For example, study reported that A. pullulans strains which delineated by phylogenetic tree showed they have distinct clade with each color formation and organic material production such as xylanase, feruloyl esterase, and pullulan.…”
Section: Identification and Phylogenetic Analysismentioning
confidence: 99%
“…The ascomycete genus Aureobasidium is a member of the family Aureobasidiaceae within the class of the Dothideomycetes (Thambugala et al 2014 ; Wijayawardene et al 2014 ). Kabatiella is closely related to Aureobasidium based on morphology and phylogeny (Zalar et al 2008 ; Bills et al 2012 ; Crous et al 2011 ; Peterson et al 2013 ; Thambugala et al 2014 ) and some of these Kabatiella species may belong to Aureobasidium (Peterson et al 2013 ; Thambugala et al 2014 ). In addition future studies may result in the transfer of the species Selenophoma mahoniae and Columnosphaeria ( Discosphaerina ) fagi into Aureobasidium (Yurlova et al 1999 ; Peterson et al 2013 ; Thambugala et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kabatiella is closely related to Aureobasidium based on morphology and phylogeny (Zalar et al 2008 ; Bills et al 2012 ; Crous et al 2011 ; Peterson et al 2013 ; Thambugala et al 2014 ) and some of these Kabatiella species may belong to Aureobasidium (Peterson et al 2013 ; Thambugala et al 2014 ). In addition future studies may result in the transfer of the species Selenophoma mahoniae and Columnosphaeria ( Discosphaerina ) fagi into Aureobasidium (Yurlova et al 1999 ; Peterson et al 2013 ; Thambugala et al 2014 ). A well-known Aureobasidium species is Aureobasidium pullulans (Zalar et al 2008 ; Gostinčar et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%